2019
DOI: 10.1039/c9cp00093c
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between electrical conductivity and second-order Raman modes of laser-reduced graphene oxide

Abstract: Second-order Raman modes correlate with the electrical properties of reduced graphene oxide measured at the nanoscale by atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 49 publications
5
78
0
1
Order By: Relevance
“…This is achieved by chemically modifying the graphene surface with soft substances or solid inorganic materials [19]. Ma et al carried out current-sensing atomic force microscopy (CSAFM) experiments for laser-reduced graphene oxide (r-GO) [20]. One revealed that after laser reduction, the high-conductivity r-GO spots appear on the graphene oxide surface in the form of two-dimensional torus shapes of several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by chemically modifying the graphene surface with soft substances or solid inorganic materials [19]. Ma et al carried out current-sensing atomic force microscopy (CSAFM) experiments for laser-reduced graphene oxide (r-GO) [20]. One revealed that after laser reduction, the high-conductivity r-GO spots appear on the graphene oxide surface in the form of two-dimensional torus shapes of several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…missing carbons, extra carbons, or carbon substitutions in the structure) [49]. The I D /I G intensity ratio increases with disorder and correlates with reduced charge carrier mobility [50]; the I D /I G ratio of the thin film in this work was equal to~0.4, typical for ultrasonic exfoliation synthesis [46,51,52]. This I D /I G intensity ratio is also inversely proportional to crystallite size, calculated to be 11 nm in this work [53].…”
Section: Resultsmentioning
confidence: 99%
“…By plotting the second-order Raman modes area vs. laser power we could obtain an idea of the optimal irradiation conditions that maximize conductivity. 52 By using those same samples in chemical sensors one could then correlate the electrical conductivity, chemical sensitivity, and crystallinity to determine the best conditions that maximize sensor performance.…”
Section: Applications Of Laser-irradiated Mod-g: a Gas Sensor And A Fmentioning
confidence: 99%